Analisis Teknik Pointing High-Lob menggunakan Jenis Lapangan Beton dalam Cabang Olahraga Petanque - Fajar Ula Rizqi; Achmad Widodo; Heri Wahyudi; Hijrin Fithroni (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to analyze the effect of high-lob technique on petanque sport pointing using a concrete field surface. The method used is descriptive research with implementation at the Petanque Laboratory of Surabaya State University. The subjects of the study were five Unesa petanque athletes who were selected based on their technical skills. Data collection techniques include field observation, skill tests, documentation, and data analysis using the Kinovea and Capcut applications. The results showed that at a distance of 6 meters, the release angle was 63.5°, the height was 3.53 m, the rolling distance was 35 cm, and the final result was 8.5 cm. At a distance of 7 meters, the release angle was 63.4°, the height was 4.01 m, the rolling distance was 53 cm, and the final result was 10.4 cm. At a distance of 8 meters, the release angle was 62.3°, the height was 3.99 m, the rolling distance was 59 cm, and the final result was 13.4 cm. Meanwhile, at a distance of 9 meters, the release angle is 60.3°, the height is 4.16 m, the roll is 53 cm, and the final result is 19.2 cm. All parameters have met the effectiveness criteria based on existing references, except for the rolling distances at 7, 8, and 9 meters which exceed the ideal limit. These results imply that adjusting the drop point and increasing the angle and height of the bounce can optimize the results of the high-lob pointing technique.